Metalla‐Assembled Electron‐Rich Tweezers: Redox‐Controlled Guest Release Through Supramolecular Dimerization. (20th November 2019) - Krykun, Serhii; Dekhtiarenko, Maksym; Canevet, David; Carré, Vincent; Aubriet, Frédéric; Levillain, Eric; Allain, Magali; Voitenko, Zoia; Sallé, Marc; Goeb, Sébastien
Abstract: Developing methodologies for on‐demand control of the release of a molecular guest requires the rational design of stimuli‐responsive hosts with functional cavities. While a substantial number of responsive metallacages have already been described, the case of coordination‐tweezers has been less explored. Herein, we report the first example of a redox‐triggered guest release from a metalla‐assembled tweezer. This tweezer incorporates two redox‐active panels constructed from the electron‐rich 9‐(1, 3‐dithiol‐2‐ylidene)fluorene unit that are facing each other. It dimerizes spontaneously in solution and the resulting interpenetrated supramolecular structure can dissociate in the presence of an electron‐poor planar unit, forming a 1:1 host–guest complex. This complex dissociates upon tweezer oxidation/dimerization, offering an original redox‐triggered molecular delivery pathway. Abstract : Überanspruchte Gastfreundschaft : Eine redox‐aktive, aus einem Dithiolfluoren‐Gerüst aufgebaute Koordinations‐„Pinzette" dimerisiert spontan in Lösung aufgrund günstiger geometrischer und elektronischer Parameter. Das verzahnte Dimer kann durch Bildung eines 1:1‐Wirt‐Gast‐Komplexes in Anwesenheit eines elektronenarmen Gastmoleküls dissoziieren. Der Gast kann wiederum reversibel durch Oxidation in einem Austauschprozess freigesetzt werden.